A complicated love story set in space - Hutchinson, Shaun David (Simon & Schuster BFYR, 2021)
Sixteen-year-olds Noa, DJ, and Jenny awake on a spaceship, unaware of how they got there or what is coming, but soon Noa and DJ are falling in love.